The Usage of Online Dictionary and Translation among Student in University - Khatimah, Khusnul; Rahmawati, Yeni; Rachman, Dzul; Herning Puspita, Rani (International Journal of Engineering and Technology, 2019)
The present research were aimed to find out how far the satisfaction level of non English department students in using online dictionary and translation and to determine the aspects involved in using online translation for comprehending material in English. This study was conducted due to many phenomenon have been noticed around the students’ life. This research was correlation study among student’s satisfaction and aspects involved it. 175 students selected as a respondents to conduct the data by using purposive sampling from the total of first year non English department student in UMKT Samarinda East Kalimantan. Questionnaire was applied as an instrument to obtain the data.  The data analyzed quantitatively was computed by using Statictical analysis. Content validity and reliability was ensured. The reliability of several constructs was larger than the 0.7 threshold. The result showed that there was significant relationship between Google Translate (GT) and student satisfaction it was showed by the moderate correlation (.670**). The aspects which influence student’s satisfaction on using GT were self efficacy, system function, and perceived usefulness. For future researcher suggested constructing the comparison among student in using online dictionary and vice versa.